2009
DOI: 10.1016/j.virol.2008.10.035
|View full text |Cite
|
Sign up to set email alerts
|

SV40 lymphomagenesis in Syrian golden hamsters

Abstract: Simian virus 40 (SV40) isolates differ in oncogenic potential in Syrian golden hamsters following intraperitoneal inoculation. Here we describe the effect of intravenous exposure on tumor induction by SV40. Strains SVCPC (simple regulatory region) and VA45-54(2E) (complex regulatory region) were highly oncogenic following intravenous inoculation, producing a spectrum of tumor types. Three lymphoma cell lines were established; all expressed SV40 T-antigen, were immortalized for growth in culture, and were tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 43 publications
(83 reference statements)
0
24
0
Order By: Relevance
“…The precision of amplification of the vimentin target gene was assessed by measuring known quantities of two hamster lymphoma cell lines (McNees et al, 2008). The RQ-PCR assay was sensitive and reproducible up to 5 × 10 5 cell equivalents/reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of amplification of the vimentin target gene was assessed by measuring known quantities of two hamster lymphoma cell lines (McNees et al, 2008). The RQ-PCR assay was sensitive and reproducible up to 5 × 10 5 cell equivalents/reaction.…”
Section: Resultsmentioning
confidence: 99%
“…This observation was compatible with earlier reports of recovery of infectious virus and/or infectious viral DNA from SV40 tumor cells (Black and Rowe, 1964; Boyd and Butel, 1972; Gerber, 1964; Sabin and Koch, 1963). Many virus-inoculated, tumor-free animals developed antibodies to T-ag that persisted for one year following either intraperitoneal or intravenous exposure (McNees et al, 2008; Sroller et al, 2008). The percentage of T-antibody responders among tumor-free hamsters was higher for those inoculated with viruses having complex regulatory regions as compared to those with simple enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…The mAbs were developed from mice immunized with hamster peripheral blood leukocytes (HAB), thymocytes (HAT), lymph node mononuclear cells (HAL), or a mixture of non-adherent and adherent mononuclear splenocytes (HASA) (Davis et al, 1987, McNees et al, 2009). Additional mAbs screened for cross reactivity to hLDMs were from commercial sources and the WSU Monoclonal Antibody Centre http://vmp.vetmed.wsu.edu/resources/monoclonal-antibody-center…”
Section: Methodsmentioning
confidence: 99%
“…Subcutaneous inoculation usually results in sarcomas at the site of injection; intrapleural and intraperitoneal inoculation leads to a high proportion of mesotheliomas (Cicala et al 1993 ;Sroller et al 2008 ) ; intracerebral inoculation produces ependymomas (Kirschstein and Gerber 1962 ) ; and intravenous inoculation induces a spectrum of tumors, especially lymphomas, mesotheliomas, and osteosarcomas (Diamandopoulos 1973 ;Carbone et al 1989 ;McNees et al 2009 ) . These studies showed that SV40 has a broad tissue tropism with the capacity to transform a variety of target cell types.…”
Section: Hamster Model Of Sv40 Infection and Oncogenesismentioning
confidence: 99%
“…First, many virus-inoculated but tumor-free animals develop antibodies to SV40 T-ag, with more responders among animals inoculated with 2E viruses as compared to 1E viruses (Sroller et al 2008 ;McNees et al 2009 ) . SV40 T-ag is not a component of the virus particle, but rather is synthesized in infected cells.…”
Section: Infl Uence Of Viral Regulatory Region On Tumor Induction Andmentioning
confidence: 99%